Signal propagation in metal-rich railway environment. Issue 4 (2nd July 2018) - Nikolic, Bojana; Dimitrijevic, Bojan; Hutschenreuther, Tino; Toepfer, Hannes
Abstract : Purpose: The purpose of this paper is to analyze a signal propagation in highly metalized environments, which has not been extensively studied in the literature. Having in mind a large number of such applications, better understanding and possibly finding a way of improving communication in these conditions would be highly beneficial. Design/methodology/approach: The analysis is performed in a simulation environment developed by the authors, based on finite difference time domain (FDTD) method, to identify effects that have decisive influence on electromagnetic (EM) wave propagation in the aforementioned conditions. The analysis of the EM field at the reception is modified so that a multiple-field sampling is performed, and maximal values are further used. In practical realizations, this procedure could be implemented by using multiple antennas and selective combining at the reception. Findings: Results show that the existence of metal objects (in the observed case, these are railway tracks), in combination with the appropriate choice of antenna parameters, can be favorably used to improve signal reception. The contribution is manifested through the reduction of the pathloss. Research limitations/implications: In the performed analysis, one should be aware of the limitations that the FDTD method brings. Those limitations are related to the size of the computational domain and discretization mesh refinement (possibility of modeling geometry in fine details). Originality/value: Originality of this paper consists of the introduced modification in the analysis of signal propagation in heavily metalized environment. Namely, a multiple-field sampling in the reception zone (in one plane, dimensions λ × λ = 12.5 cm X 12.5 cm) is performed using several probes in simulation environment. In this way, a qualitative analysis is performed more efficiently, which made it is possible to distinguish and identify different propagation mechanisms.